Corrosion and corrosion-fatigue synergism on the base metal and nugget zone of the 2524-T3 Al alloy joined by FSW process. (15th April 2021) - Moreto, J.A.; dos Santos, M.S.; Ferreira, M.O.A.; Carvalho, G.S.; Gelamo, R.V.; Aoki, I.V.; Taryba, M.; Bose Filho, W.W.; Fernandes, J.C.S.
Graphical abstract: Highlights: Microstructural studies of 2524-T3 Al alloy welded by FSW were performed. Corrosion resistance of the base material and nugget zone was assessed by EIS and SVET. Base material and nugget zone possess a cathodic behaviour. The influence of FSW process on FCG curves in nugget and base material was studied. Abstract: The corrosion processes and its influence on the FCG curves of the 2524-T3 alloy joined by FSW was studied in the nugget and BM. To assess the corrosion process, SVET, pH micro-potentiometry and EIS were used. The localised corrosion results showed similar BM and nugget zone electrochemical behaviour, while the TMAZ/HAZ region was electrochemically the weakest zone, susceptible to anodic dissolution. The FSW process and saline environment was found to modify the BM and nugget FCG resistance, being more detrimental for the BM due to the primary IM particles that are not present in the nugget, making it chemically more homogeneous.